Continuous-flow combined process of nitritation and ANAMMOX for treatment of landfill leachate. (August 2016) - Wang, Zhong; Peng, Yongzhen; Miao, Lei; Cao, Tianhao; Zhang, Fangzhai; Wang, Shuying; Han, Jinhao
Abstract : Graphical abstract: Highlights: A continuous-flow process of nitritation and ANAMMOX was used to treat leachate. The mature landfill leachate without diluted by tap-water was used in this study. Associated inhibition of FA and FNA to NOB facilitate realization of nitritation. The conversion rate of NH4 + -N and NAR in A/O were up to 95% and 92%, respectively. Quantitative PCR analyzed the proportions of AOB, NOB and anammox in A/O and UASB. Abstract: Due to the difficulty in removing nitrogen from landfill leachate, a combined continuous-flow process of nitritation and anammox was applied to process mature leachate. The transformation rate of ammonia and nitrite accumulation ratio in A/O reactor were kept above 95% and 92% respectively through associated inhibition of free ammonia (FA) and free nitrous acid (FNA) to NOB. The total nitrogen volumetric load of anammox in an UASB reactor was brought up from 0.5 kg/(m 3 ·d) to 1.2 kg/(m 3 ·d) by gradually increasing influent substrate concentration and reducing hydraulic retention time (HRT). The results show that COD from mature leachate did not bring obvious inhibition effects to anammox. Under concentrations of influent ammonia and COD which were respectively 1330 mg/L and 2250 mg/L, the removal efficiencies of TN and COD reached 94% and 62% respectively. In the quantitative PCR reactions, the proportions occupied by AOB, NOB and anammox in A/O were 11.39%, 1.76% and 0.05% respectively; and proportions of those in UASB were 0.35%, 4.01% and 7.78% respectively.